Analisis Daya Saing Mahasiswa Prestasi Akademik, Pengalaman Magang, Kompetensi, dan Motivasi Kerja terhadap Kesiapan Kerja pada Mahasiswa Fakultas Ekonomi Universitas Gunadarma - Adhitia Kusuma Wardana; Mohammad Abdul Mukhyi (Jurnal Manajemen Bisnis Era Digital, 2025)
With the advancement of technology and globalization, technical skills alone are no longer sufficient to face the increasingly complex challenges of the workplace. Students are expected to possess soft skills such as communication, leadership, teamwork, and critical thinking and problem-solving skills frequently encountered in the professional world. This study aims to analyze the level of achievement, experience, work motivation, and competency on work readiness among students at Gunadarma University, Karawaci Region. The analysis method used quantitative primary data, with the following testing stages: convergent validity, discriminant validity, reliability, r-square, q-square, f-square, and path coefficients. The instrument used was a questionnaire, and valid data was collected from 250 respondents. The sampling method in this study was non-probability sampling with a purposive sampling technique. The testing tool used was SmartPLS. The results of this study indicate that the variables of achievement level, experience, work motivation, and competence influence work readiness among Gunadarma University students in the Karawaci region.